2015
DOI: 10.1039/c5sc01104c
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer versus molecular conductance: molecular orbital symmetry turns quantum interference rules upside down

Abstract: Molecular orbital symmetry considerations can strongly affect the nature of quantum interference effects in charge transfer..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 61 publications
3
41
0
Order By: Relevance
“…These are shown in Figure 2a, left panel; the arrows point the direction of net current flow from the left to the right electrode. E −E F = −1.00 eV, constructively interact, which are consistent with those previous results 43 . The antiresonance can be characterized by the reversal of ring currents 58 .…”
Section: Using the Negf-dft Approach The Main Features Of Pdos And Tsupporting
confidence: 93%
See 2 more Smart Citations
“…These are shown in Figure 2a, left panel; the arrows point the direction of net current flow from the left to the right electrode. E −E F = −1.00 eV, constructively interact, which are consistent with those previous results 43 . The antiresonance can be characterized by the reversal of ring currents 58 .…”
Section: Using the Negf-dft Approach The Main Features Of Pdos And Tsupporting
confidence: 93%
“…In the case of NH 3 , the sharp dip in T (E) appears at ∼ -1.21 eV below the Fermi energy indicating antiresonance. For BPDT without gas adsorption, a previous study 43 has demonstrated that large transmission near the Fermi energy results from constructive contributions from HOMO and LUMO. These are shown in Figure 2a, left panel; the arrows point the direction of net current flow from the left to the right electrode.…”
Section: Using the Negf-dft Approach The Main Features Of Pdos And Tmentioning
confidence: 96%
See 1 more Smart Citation
“…Destructive quantum interference (DQI) is one notable exception to this principle. Some molecules (such as benzene) have multiple paths [6,7] for transporting electrons across the junction, and these paths may destructively interfere with each other to suppress or even block current [8][9][10][11]. From an applications perspective, DQI may result in good molecular insulators [3].…”
Section: Introductionmentioning
confidence: 99%
“…The link between these related fields can be seen in the general assumption that the electron transport/transfer properties of a bridging molecule will be preserved when moving from system to system. However, writing in Chemical Science, Ferdinand Grozema and colleagues 1 have now shown that this assumption can be very misleading, and that electronic properties can be very different depending on how exactly the molecule is 'wired up' .…”
mentioning
confidence: 97%